Being George Washington : the indispensable man, as you've never seen him - Beck, Glenn; Balfe, Kevin (New York : Threshold Editions/Mercury Radio Arts, 2011)
Combining biography and Washington's own writings with his own comments and sidebars, Beck explores our nation's first president and describes how Washington's beliefs and values--beliefs and values which united a country in an age even more fractious than our own--are especially important to remember today.
Keywords: Washington, George, -- 1732-1799 -- Military leadership; Presidents -- United States -- Biography; Generals -- United States -- Biography; United States -- History -- Revolution, 1775-1783.